The Role of School Principals in Enhancing Teachers' Digital Media Integration Competence - Vevy Lolita; Hendrizal Hendrizal; Siti Aisyah; Romi Kurniawan (Universitas Negeri Makassar, 2026)
This study examines the role of primary school principals in enhancing teachers’ ability to utilize digital media for instruction in Gunung Tujuh District, Indonesia. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation across three public elementary schools. Findings indicate that teachers’ digital media utilization remains at an operational-applicative level, focusing on basic tools rather than pedagogically transformative integration. Principals actively function as motivators, facilitators, supervisors, and innovators, implementing initiatives such as professional learning communities, peer mentoring, and targeted competency programs. Key supporting factors include teacher motivation, collaborative school culture, and committed leadership, while primary inhibitors encompass unstable internet connectivity, limited hardware, excessive administrative workloads, and generational disparities in digital literacy. The study concludes that while principals successfully foster an adaptive learning climate through humanistic leadership, sustainable digital transformation requires institutionalized competency development, data-driven academic supervision, and systemic policy support to mitigate infrastructural and workload constraints.